PAW28 The natural history of multiple sclerosis, a geographically based study. 10: relapses and long-term disability. Issue 11 (22nd October 2010) - Ebers, G; Neuhaus, A; Muraro, P; Daumer, M; Harner, N; Degenhardt, A; Rice, G P; Scalfari, A
Abstract : The relationship of relapses to long-term disability in multiple sclerosis (MS) is uncertain. The reduction of relapses is a common therapeutic target but clinical trials have shown dissociation between relapse suppression and disability accumulation. We investigated relationships between relapses and disability progression for outcomes of needing assistance to walk, being bedridden and dying from MS (disability status scale –DSS 6, 8 and 10) by analysing 28 000 patient-years of disease evolution in 806 bout onset patients from the London Ontario natural history cohort. Clinical features evident early in the disease are strong predictors of hard disability outcomes. In contrast, neither number of relapses experienced during the relapsing remitting phase (RR) after y2 (y3-SP) nor total number of RR phase attacks showed any deleterious effect on these hard unambiguous outcomes. Higher early relapse frequencies and shorter first inter-attack intervals herald a more rapid clinical course via interaction with the neurodegeneration which characterises secondary progression in susceptible individuals. They determine an increasing probability of occurrence by shortening the latency and by influencing to a lesser degree its slope. The progressive phase of the disease and its prevention or delay are implicated as the key therapeutic targets in relapsing remitting patients.